From heart failure and kidney dysfunction to cardiorenal syndrome: TMAO may be a bridge - Zhang, Jialun; Zhu, Peining; Li, Siyu; Gao, Yufei; Xing, Yue (Frontiers in Pharmacology, 2023)
Abstract：The study of trimethylamine oxide (TMAO), a metabolite of gut microbiota, 2 and heart failure and chronic kidney disease has made preliminary achievements and been summarized by many researchers, but its research in the field of cardiorenal syndrome is just beginning. TMAO is derived from the trimethylamine (TMA) that is produced by the gut microbiota after consumption of carnitine and choline and is then transformed by flavin-containing monooxygenase (FMO) in the liver. Numerous research results have shown that TMAO not only participates in the pathophysiological progression of heart and renal diseases but also significantly affects outcomes in chronic heart failure (CHF) and chronic kidney disease (CKD), besides influencing the general health of populations. Elevated circulating TMAO levels are associated with adverse cardiovascular events such as HF, myocardial infarction, and stroke, patients with CKD have a poor prognosis as well. However, no study has confirmed an association between TMAO and cardiorenal syndrome (CRS). As a syndrome in which heart and kidney diseases intersect, CRS is often overlooked by clinicians. Here, we summarize the research on TMAO in HF and kidney disease and review the existing biomarkers of CRS. At the same time, we introduced the relationship between exercise and gut microbiota, and appropriately explored the possible mechanisms by which exercise affects gut microbiota. Finally, we discuss whether TMAO can serve as a biomarker of CRS, with the aim of providing new strategies for the detection, 3 prognostic, and treatment evaluation of CRS. Keyword：trimethylamine oxide, heart failure, chronic kidney disease, cardiorenal syndrome, trimethylamine